Energy and exergy analyses of novel supercritical CO2 Brayton cycles driven by direct oxy-fuel combustor - Ahmad K. Sleiti (14778229) (2021)
This study addresses major research gaps related to supercritical carbon dioxide (sCO2) power cycles including the shortcomings due to adding extra components, the high operating temperatures and the lack of studies on using direct oxy-combustion for sCO2 power cycles. Energy and exergy analyses for five novel sCO2 Brayton cycles with direct oxy-fuel combustion are introduced. The studied cycle configurations are the simple recuperator cycle (SRC), dual recuperator cycle (DRC), intercooling cycle (ICC), reheating cycle (RHC) and partial intercooling cycle (PIC). A numerical model was developed for the detailed calculations of the recuperators that considers variations in the properties of sCO2 as a function of temperature. Comprehensive studies and optimization are performed for the major parameters including the pressure ratio (rc), intermediate pressure ratio (RPR), turbine inlet temperature (TIT) and compressor inlet temperature (CIT). Optimum rc and RPR values have been obtained at which the maximum efficiencies of the cycles occur. Results show that the partial intercooling cycle (PIC) has superior performance compared to the other configurations at higher TIT and lower PRR. The maximum thermal efficiency of 52% is achieved by the PIC at rc of 5, RPR of 0.45, TIT of 750 °C, high pressure of 20 MPa, and CIT of 50 °C. Furthermore, the reheating cycle has the highest second law efficiency with marginal improvement in the thermal efficiency compared to the dual recuperator cycle (DRC). Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2021.120557